Recent advances in catalytic enantioselective direct C–H bond functionalization of electron-deficient N-containing heteroarenes. Issue 1 (15th October 2021) - Liu, Xiao-Lan; Jiang, Luo-Bin; Luo, Mu-Peng; Ren, Zhi; Wang, Shou-Guo
Abstract : Catalytic enantioselective direct C–H bond functionalization of electron-deficient N-containing heteroarenes represents one of the most straightforward and powerful protocols to construct diverse enantioenriched highly functionalized N-heteroarenes. Abstract : Catalytic enantioselective direct C–H bond functionalization of electron-deficient N-containing heteroarenes represents one of the most straightforward and powerful protocols to construct diverse enantioenriched highly functionalized N-heteroarene products. Efficient catalytic systems and a variety of strategies for highly chemo- and stereoselective C–H functionalization of electron-deficient N-containing heteroarenes have been developed over the past few decades. This review summarized the rapid progress in the catalytic asymmetric C–H functionalization of N-containing heteroarenes and discussed the challenges and potential of the field in the current stage.